The Oxford handbook of business and government - Coen, David, 1967-; Grant, Wyn.; Wilson, Graham K. (Oxford : Oxford University Press, 2010)
This text provides an introduction to the ways in which five different disciplines have approached the study of business and government. It examines how business interacts with government in different parts of the world, including the United States the EU, China, Japan and South America.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Business and politics; Industrial policy; Political planning